Reporting on antibiotic use patterns using the WHO Access, Watch, Reserve classification in the Caribbean - Tamarie Rocke; Nathalie El Omeiri; Rodolfo Ernesto Quiros; Jenny Hsieh; Pilar Ramon-Pardo (Pan American Health Organization, 2022)
Objective. To assess antibiotic use in three hospitals in three Caribbean countries based on data from 2013 and 2018 using the World Health Organization Essential Medicines List "Access, Watch, Reserve" (AWaRe) classification. Methods. A retrospective observational study, which analyzed the World Health Organization Point Prevalence Survey data from three hospitals in three Caribbean countries, to examine proportional AWaRe group antibiotic use for the top ten inpatient indications. The Access-to-Watch ratio was calculated, and the top three antibiotics prescribed in each hospital were determined. Results. The final data set included 376 prescriptions for the top ten indications in 766 inpatients. The hospital antibiotic use point prevalence for Hospital 1 was 35.6%, Hospital 2 was 48.6%, and Hospital 3 was 47.1%. The Access-to-Watch ratio for the top ten indications was 2.45, 1.36, and 1.72 in the three hospitals. Access group prevalence was 71.0% in Hospital 1, 57.6% in Hospital 2, and 63.2% in Hospital 3. There were no Reserve antibiotics prescribed in any of the institutions. The most common indication for Watch prescription was skin and soft tissue infections in Hospital 1 and pneumonia in Hospital 2 and 3. Conclusions. This study draws urgent attention to evidence of a high proportion of Watch antibiotic prescribing and lack of Reserve group antibiotics in three Caribbean countries. This research provides data that may inform national formulary and antimicrobial stewardship policy-making across the settings analyzed and the wider region.